A Versatile Route to Assemble Semiconductor Nanoparticles into Functional Aerogels by Means of Trivalent Cations. Issue 16 (12th March 2020) - Zámbó, Dániel; Schlosser, Anja; Rusch, Pascal; Lübkemann, Franziska; Koch, Julian; Pfnür, Herbert; Bigall, Nadja C.
Abstract: 3D nanoparticle assemblies offer a unique platform to enhance and extend the functionality and optical/electrical properties of individual nanoparticles. Especially, a self‐supported, voluminous, and porous macroscopic material built up from interconnected semiconductor nanoparticles provides new possibilities in the field of sensing, optoelectronics, and photovoltaics. Herein, a method is demonstrated for assembling semiconductor nanoparticle systems containing building blocks possessing different composition, size, shape, and surface ligands. The method is based on the controlled destabilization of the particles triggered by trivalent cations (Y 3+, Yb 3+, and Al 3+ ). The effect of the cations is investigated via X‐ray photoelectron spectroscopy. The macroscopic, self‐supported aerogels consist of the hyperbranched network of interconnected CdSe/CdS dot‐in‐rods, or CdSe/CdS as well as CdSe/CdTe core‐crown nanoplatelets is used to demonstrate the versatility of the procedure. The non‐oxidative assembly method takes place at room temperature without thermal activation in several hours and preserves the shape and the fluorescence of the building blocks. The assembled nanoparticle network provides longer exciton lifetimes with retained photoluminescence quantum yields, that make these nanostructured materials a perfect platform for novel multifunctional 3D networks in sensing. Various sets of photoelectrochemical measurements on the interconnected semiconductor nanorod structures also reveal the enhanced charge carrier separation. Abstract : Self‐assembly of cadmium chalcogenide quantum rods and nanoplatelets into functional aerogels is carried out by means of trivalent cations. Regardless of size, shape, composition and surface ligands, macroscopic, voluminous, fluorescent 3D gel networks can be formed, where the building blocks are interconnected, therefore an effective charge‐carrier separation can be achieved, that makes them potential candidates for photoelectrochemical sensing purposes.